Molecular features of hepatosplenic T-cell lymphoma unravels potential novel therapeutic targets - Travert, Marion; Huang, Yenlin; de Leval, Laurence; Martin-Garcia, Nadine; Delfau-Larue, Marie-Helene; Berger, Françoise; Bosq, Jacques; Brière, Josette; Soulier, Jean; MacIntyre, Elizabeth; Marafioti, Teresa; de Reyniès, Aurélien; et al. (Blood, 2012)
The pathogenesis of hepatosplenic T-cell lymphoma (HSTL), a rare entity mostly derived from γδ T cells and usually with a fatal outcome, remains largely unknown. In this study, HSTL samples (7γδ and 2αβ) and the DERL2 HSTL cell line were subjected to combined gene-expression profiling and array-based comparative genomic hybridization. Compared with other T-cell lymphomas, HSTL had a distinct molecular signature irrespective of TCR cell lineage. Compared with peripheral T-cell lymphoma, not otherwise specified and normal γδ T cells, HSTL overexpressed genes encoding NK-cell–associated molecules, oncogenes (FOS and VAV3), the sphingosine-1-phosphatase receptor 5 involved in cell trafficking, and the tyrosine kinase SYK, whereas the tumor-suppressor gene AIM1 (absent in melanoma 1) was among the most down-expressed. We found highly methylated CpG islands of AIM1 in DERL2 cells, and decitabine treatment induced a significant increase in AIM1 transcripts. Syk was present in HSTL cells and DERL2 cells contained phosphorylated Syk and were sensitive to a Syk inhibitor in vitro. Genomic profiles confirmed recurrent isochromosome 7q (n = 6/9) without alterations at the SYK and AIM1 loci. Our results identify a distinct molecular signature for HSTL and highlight oncogenic pathways that offer rationale for exploring new therapeutic options such as Syk inhibitors and demethylating agents.